2021
DOI: 10.21203/rs.3.rs-535213/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population Snapshot of the Extended-spectrum β-lactamase-producing Escherichia Coli Invasive Strains Isolated From a Hungarian Hospital

Abstract: Background:This study was carried out to determine the prevalence and the genetic background of extended-spectrum β-lactamase-producing Escherichia coli invasive isolates obtained from a tertiary-care hospital in Budapest, Hungary. MethodsBetween October-November 2018, all invasive ESBL-producing E. coli isolates were collected from Central Hospital of Southern Pest. The antimicrobial susceptibility testing was performed according to the EUCAST guidelines. The possible clonal relationships were investigated by… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
1
Order By: Relevance
“…However, a recent study found ST131 clade A strains isolated from wastewater harboured a higher prevalence of fluoroquinolone resistance compared with clade C strains [65]. In our study, the ST69 strain AGR6137 carried a qnrB1 gene, which has previously been found to be carried by bla CTX-M-15 plasmids [66][67][68] but to our knowledge rarely in bla CTX-M-27 plasmids.…”
Section: Distribution Of Amr and Virulence Genescontrasting
confidence: 41%
“…However, a recent study found ST131 clade A strains isolated from wastewater harboured a higher prevalence of fluoroquinolone resistance compared with clade C strains [65]. In our study, the ST69 strain AGR6137 carried a qnrB1 gene, which has previously been found to be carried by bla CTX-M-15 plasmids [66][67][68] but to our knowledge rarely in bla CTX-M-27 plasmids.…”
Section: Distribution Of Amr and Virulence Genescontrasting
confidence: 41%